Exploring the Relationship between Mentorship and Successful Youth Entrepreneurship at Telkom, South Africa - Tshehla, Belinda; Costa, King (My University, 2021)
South Africa, in general, is plagued by high unemployment, especially among the youth. The study explored the relationship between mentorship and successful youth entrepreneurship at Telkom, South Africa. The primary focus of the investigation was to establish whether mentorship could be the answer to unemployment and the declining youth entrepreneurship in the City of Tshwane. A qualitative research approach was applied in this study, using the Telkom mentorship programme as the sample. The sample consisted of mentors and youth mentees, obtained from the Telkom mentorship database. Data was collected using semi-structured, open-ended interviews. Data analysis was done using thematic analysis with Atlas Ti 8.0. The literature shows that mentoring has benefits for both mentors and entrepreneur mentees. It also shows that the government and private sector can play a key role in youth entrepreneur mentorship. The findings of the study have proven that mentorship yields positive results for youth entrepreneurs, which supports the literature in this study. The findings of the study yielded three themes, which were as follows: success factors for mentorship, inhibiting factors for mentorship, and influence of mentorship on successful youth entrepreneurship. In addressing the objectives of this study, the findings have proven that there is a relationship between mentorship and successful youth entrepreneurship. The recommendations made in this study include improvements in the mentorship programme for mentees and mentors, initiatives by government that include more mentorship programmes and better communication as well as providing funding for mentorship programmes. Further research, to establish the correlation between mentorship and successful entrepreneurship, is recommended.
Keywords: entrepreneur; entrepreneurship; mentorship; mentor; mentee; youth; unemploymen